2014
DOI: 10.2174/1381612819666131216121019
|View full text |Cite
|
Sign up to set email alerts
|

Going up in Smoke? A Review of nAChRs-based Treatment Strategies for Improving Cognition in Schizophrenia

Abstract: Cognitive impairment is known to be a core deficit in schizophrenia. Existing treatments for schizophrenia have limited efficacy against cognitive impairment. The ubiquitous use of nicotine in this population is thought to reflect an attempt by patients to self-medicate certain symptoms associated with the illness. Concurrently there is evidence that nicotinic receptors that have lower affinity for nicotine are more important in cognition. Therefore, a number of medications that target nicotinic acetylcholine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 224 publications
(234 reference statements)
0
20
0
Order By: Relevance
“…Nicotine use is increased in schizophrenia patients, where it has cognitive benefits (Boggs et al, 2014). Also nicotine increases visual attention and working memory in healthy volunteers (Ernst et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine use is increased in schizophrenia patients, where it has cognitive benefits (Boggs et al, 2014). Also nicotine increases visual attention and working memory in healthy volunteers (Ernst et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review stated that α7nAChR-agonists induce beneficial effects in patients with psychiatric disorders (139) ameliorating cognitive deficits, negative symptoms, and sensory gating disturbances in both preclinical and clinical trials of schizophrenia (139, 157161). Advantageous effects for the negative symptoms have been reported repeatedly, while improvements in the cognitive domain remain controversial, deserving further exploration (175, 176). Together, these studies indicate that the vagus nerve and the α7nAChR may be involved in the inflammatory hypothesis of schizophrenia (Figure 1).…”
Section: Does Autonomic Immunomodulation Contribute To the Inflammatomentioning
confidence: 99%
“…In addition to being an acetylcholinesterase inhibitor, galantamine is an allosteric acetylcholine receptor (nAChR) modulator and a number of data have shown that treatments increasing nAChr activity may improve schizophrenia cognitive symptoms [60]. Two schizophrenia patients treated with galantamine (8-10 mg/day) showed improvement in attention and speech after 12-20 days [61].…”
Section: Galantaminementioning
confidence: 99%